Cape Verde : Sixth Review Under the Policy Support Instrument and Request for a One-Year Extension of the Policy Support Instrument; Staff Report; Press Release. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the Sixth Review under the Policy Support Instrument (PSI) for Cape Verde. Policy implementation under the PSI-supported program continues to be strong; all PSIs quantitative targets except for one at end-December 2008 were met. In 2009, real GDP growth is expected to decelerate as external demand and private sector growth weakens. IMF staff recommends completion of the sixth PSI review and granting of the waiver on the nonobservance of the assessment criterion on net domestic assets of the Bank of Cape Verde.